Samodzielne przedsiębiorstwo komunalne prawa publicznego w systemie publicznoprawnych form organizacyjnych świadczenia usług materialnych przez gminy w Republice Federalnej Niemiec - Miemiec, Marcin (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
German municipalities provide intangible and tangible (economic) services to the members of their self-governmental municipalities. Intangible and tangible services are provided by entities that are part of the system — under private-law (capital companies) or public-law (administrative companies or other forms of public-law companies that are independent of their municipalities and separated from the municipality executive apparatus). The subject matter of this study is the administrative company, generally referred to as amunicipal company under the public law. In the German territorial self-government, it is arelatively new legal entity that was established in the mid-nineties of the twentieth century. Although it has apersonality under the public law, its regime is largely based on capital companies. Compared to other entities — proprietary company or managed company — it has relatively wide independence of its municipalities. Thus, it is often referred to as aform of inner-municipal decentralization. However, the municipality may have alarger influence on such a company’s organization and functioning compared to capital companies in which it holds shares.
Keywords: territorial self-government; municipality; tangible (economic) and intangible municipality services; municipal company under public law